Exploring the Muslim-friendly attributes in Taiwan toward travels’ visit decision: the moderating role of religiosity - Achlan Fahlevi Royanow; Putri Rizkiyah; Ali Muhtasom; Amirosa Ria Satiadji; Saiful Fahmi; Li-Wei Liu; Pahrudin Pahrudin (Cogent Social Sciences, 2024)
This study aims to explore the Muslim-friendly attributes in non-Muslim countries, such as Taiwan, from the perspective of Muslim travelers while deciding whether to visit a non-Muslim destination. The total number of respondents was 233 Muslim travelers who had decided to visit Taiwan. This study employed Structural Equation Modeling-Partial Least Square (SEM-PLS) second-order analysis to examine the hypotheses of Muslim-friendly attributes on cognitive and affective destination image, religiosity, and decision to visit. The result finds that Muslim-friendly tourism significantly impacts cognitive and affective destination image. Meanwhile, the Muslim-friendly tourism attribute is insignificant in the decision to visit. This study contributes to the Muslim-friendly tourism literature in non-Muslim countries from the perspective of the most-Muslim traveler population country by developing a construct for Muslim tourism destinations regarding the religiosity component. For practical contribution, this study gives insight for traveler agencies, tourism marketers, and stakeholders collaborate to provide Muslim-friendly tourism attributes in non-Muslim countries especially in Taiwan to increase the number of visitors from Muslim travelers.